Comparison of Stone Clearance in Mini-Percutaneous Nephrolithotomy Versus Extracorporeal Shock Wave Lithotripsy in Patients with Small Renal Calculi - Arshad, Jawad; Siddiqui, Muhammad Ejaz; Ahmad, Muhammad Zahid; Islam, Shams Ul; Zubair, Maira; Gohar, Esha (Biological and Clinical Sciences Research Journal, 2025)
Nephrolithiasis is a common urological condition, with prevalence ranging between 1% and 19.1% in South Asia, including Pakistan. Management depends on stone size, location, and patient characteristics. Extracorporeal Shock Wave Lithotripsy (ESWL) is a non-invasive treatment with variable success rates. In contrast, mini-percutaneous nephrolithotomy (mini-PCNL) is a minimally invasive procedure that offers higher stone clearance rates. The choice of modality is crucial for stones ≤1.5 cm, where an optimal balance between efficacy and invasiveness is required. Objective: To compare stone clearance rates between mini-PCNL and ESWL in patients with small renal calculi (≤1.5 cm). Methods: This randomized controlled trial was conducted at the Department of Urology, Sir Ganga Ram Hospital, Lahore, in collaboration with Jinnah Hospital, Lahore, from November 2024 to April 2025. Ninety-two patients who met the eligibility criteria were randomized into two groups: Mini-PCNL (n = 46) and ESWL (n = 46). Data on demographics, stone size, and location were recorded. Stone clearance was defined as the absence of residual calculi confirmed by ultrasound KUB and X-ray KUB—on postoperative day 1 for mini-PCNL and at 4 weeks for ESWL. Data were analyzed using SPSS v22. A chi-square test was applied, with a p-value of ≤ 0.05 considered statistically significant. Results: The mean age was 35.8 ± 12.9 years, with males comprising 73.9% of the sample. The mean stone size was 11.2 ± 3.3 mm. The overall stone-free rate was 64.1%. In the mini-PCNL group, stone-free rate was 65.2% compared to 63% in the ESWL group (p = 0.82). Subgroup analysis revealed that for stones 10–15 mm, mini-PCNL achieved a significantly higher clearance (65.2%) compared to ESWL (29.4%). Stones <10 mm, present only in the ESWL group, showed an 86.2% clearance rate. Conclusion: Mini-PCNL and ESWL showed comparable overall clearance rates for renal stones ≤1.5 cm. However, ESWL was more effective for stones <10 mm, while mini-PCNL demonstrated superior clearance for stones 10–15 mm. Thus, ESWL is preferable for smaller calculi, whereas mini-PCNL should be considered for larger stones requiring a single-session definitive treatment.